Relationship between mental health and personal development in the student youth - TERLETSKA, Larisa; VASYLENKO, Yulia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2024)
B a c k g r o u n d . The article presents the results of research on the concept of mental health and personal development. The purpose of the study: to study the relationship between mental health and personal development of student youth.M e t h o d s . To solve the tasks, the work used methods of theoretical and empirical research: a) theoretical methods – analysis, classification, types, and generalization – made it possible to scientifically and theoretically substantiate the data we received; b) empirical methods – diagnostic methods (J. Rotter's "Locus of Subjective Control" methodology and the Questionnaire "Self-Assessment of Anxiety, Frustration, Aggressiveness, and Rigidity"), comparative analysis of research results, and mathematical data processing methods.R e s u l t s . During this study, it was found that the mental health and personal development of students are closely interconnected and significantly affect their academic performance, career prospects and general well-being. The results of the study indicate that a low level of anxiety, frustration, aggressiveness, and rigidity contributes to an active life position, striving for achievements, initiative, and responsibility.C o n c l u s i o n s . Specific features of mental health and personal development of students are determined. The student period is a dynamic and transitional stage of a person's life, characterized by significant psychosocial changes. It is accompanied by intensive training, the search for one's own identity and place in life, as well as adaptation to new social conditions. Mental health plays a critical role in the personal development of student youth, affecting academic success, social interactions, emotional well-being, and self-actualization.
Keywords: mental health; personal development; emotional well-being; anxiety; frustration; student age